2022
DOI: 10.52547/wjps.11.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Is Preemptive Oral Tizanidine Effective on Postoperative Pain Intensity after Bimaxillary Orthognathic Surgery? A Triple-Blind Randomized Clinical Trial

Abstract: Background:We aimed to investigate the effect of preoperative administration of oral tizanidine on postoperative pain intensity after bimaxillary orthognathic surgery.Methods: All healthy skeletal class III patients who were candidates for bimaxillary orthognathic surgery were enrolled in this triple-blind randomized clinical trial. The study was carried out in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The bias from the randomization process was low in all five studies. [ 9 10 11 12 13 ] Bias due to deviations from intended interventions (allocation concealment) was low in all five studies. [ 9 10 11 12 13 ] Bias arising due to missing outcome data was low in four studies[ 9 10 11 12 ] with no information in one study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The bias from the randomization process was low in all five studies. [ 9 10 11 12 13 ] Bias due to deviations from intended interventions (allocation concealment) was low in all five studies. [ 9 10 11 12 13 ] Bias arising due to missing outcome data was low in four studies[ 9 10 11 12 ] with no information in one study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9 10 11 12 13 ] Bias due to deviations from intended interventions (allocation concealment) was low in all five studies. [ 9 10 11 12 13 ] Bias arising due to missing outcome data was low in four studies[ 9 10 11 12 ] with no information in one study. [ 13 ] Bias in the measurement of outcome was low in four studies,[ 9 10 11 12 ] and there was no information in one study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the bimaxillary orthognathic procedure, Dadmehr et al reported that the introduction of oral tizanidine was successful in lowering postoperative soreness [ 28 ]. Following orthognathic surgery, acute chronic postoperatively pain can be predicted using the pain catastrophizing scale and presurgical conditioned pain modulation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%